Pattern and determinants of ocular complications in leprosy patients in eastern Nepal - Javvadhi, S; Das, H; Agrawal, S (Nepalese Journal of Ophthalmology, 2010)
Background: Ocular complications of leprosy can lead to blindness. Objective: To report the pattern and determinants of ocular complications in patients with leprosy from eastern Nepal. Methods: A cross-sectional study was carried out analyzing one hundred and eighty six patients of leprosy presenting between Jan 2002-Nov 2004. All the patients were categorized using WHO and Ridley and Jopling classification. After determining bacillary indices in all of them, a detailed ocular examination was carried out. Independent risk factors were determined for ocular involvement. Results: Ocular complications were found in 30.65 % of the leprosy patients; lagophthalmos (17.74%) was the most frequent followed by uveitis (8.60%). Most of the patients having visual loss had it due to corneal complications and none of the patients with uveitis had vision <6/18. The patients released from treatment (83.33%) and those currently on treatment (31.63%) had higher occurrence of complications. Risk factors for ocular involvement were higher bacillary index, longer disease duration (p=0.031, RR=1.109, 95% CI=1.009-01.218) and decreased corneal sensation (p=0.001, RR=3.564; 95% CI =2.014-6.306). Higher Schirmer values (p=0.012, RR=0.935, 95% CI=0.888-0.985) were found to be protective for ocular complications. Statistics: SPSS ver 10.0 was used for data analysis. The P value of <0.05 was considered as significant. Conclusions: The prevalence of complications is high in patients released from treatment for leprosy. Cornea-related complications are the most important cause of visual disability and blindness. Risk factors for ocular complications are higher bacillary index, longer disease duration and decreased corneal sensation. Key words: leprosy; Nepal; ocular complications; risk factors DOI: 10.3126/nepjoph.v1i1.3666 Nep J Oph 2009;1(1):2-8